Estimation of Emitter Spacing for Close Growing Field Crops Under Point and Disc Source Water Flow Geometries : Emitter spacing under point drip irrigation - Chhedi Lal Verma; Rohit Pratap Ojha (Journal of Soil Salinity and Water Quality, 2023)
Drip irrigation has become important method to apply irrigation water precisely with minimum field losses. It also allows use of poor-quality irrigation water safely and efficiently. Drip irrigation with its variations cover large varieties of crops in the field. Largely spaced plantations and close growing crops in lines are well suited for drip irrigation. Emitters are to be fixed over a lateral to meet the uniform water distribution criteria. Some researchers suggested that for line growing crops wetted front of individual point source emitter should touch each other. This approach of emitter spacing calculation has serious drawback of leaving dry soil on and below the soil surface in the middle of emitters. The plants may not get sufficient moisture for deep or lateral spread. Researchers have empirically suggested overlapping of wetted fronts to address this issue. An overlapping wetted front criterion was developed in the present study to minimize the dry region in the centre. Single input based effective hemi-spherical model can be used for predicting wetted front advance for surface point source. When diameter of wetted front is considered as spacing between the emitters adjacent wetted fronts should touch each other. About 27.32% of the area remains dry when wetted front touches each other. This area reduced 11.60% with overlapping wetted front criterion. Overlapping of wetted fronts may cover dry region. New spacing of (π/2)R may be used for emitter and lateral spacing calculation.